Effect of losartan and captopril on expression of cardiac angiotensin II AT1 receptor mRNA in rats following myocardial infarction - Zhang Gao-Xing; Pu Shou-Yue; Yang Ying-Zhen; Shen Xue-Dong; Peng Tian-Qing; Chen Hao-Zhu (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of losartan (Los) and captopril (Cap) treatment on expression of cardiac angiotensin II (Ang) AT1 receptor mRNA in rats following myocardial infarction (MI). METHODS: Twenty-four rats with MI after coronary ligation for 7 d were randomly divided into 4 groups: A) Cap in drinking water, ad lib (2 g.L-1), B) i.g. Los 10 mg.kg-1.d-1, C) i.g. Los 30 mg.kg-1.d-1, and D) placebo for 6 wk. Sham-ligation rats (group E) served as controls. The levels of cardiac Ang AT1 receptor mRNA expression in each group (n = 6) were examined by Dot blot using digoxigenin-labeled cDNA probes. RESULTS: Comparing with reflected peak areas of hybridization positive signals in group D (2640 +/- 201 micron 2), the expression of the cardiac Ang AT1 receptor mRNA was much lower in the 3 treated groups (group A 1360 +/- 134 micron 2, group B 1430 +/- 244 micron 2, group C 1310 +/- 95 micron 2) (P < 0.01). But no difference was found between the 3 treated groups and sham-ligation group (1230 +/- 233 micron 2) (P > 0.05). CONCLUSION: Los and Cap attenuated the increase of cardiac Ang AT1 receptor mRNA expression in rats following MI.